Analyzing Factors of Remote Leadership to Effective Communication: A Case Study of CV. Anugrah Driatama - Haritsyah, Senna; Pangestu, Aria Bayu (Journal of Business and Management, 2019)
Effective communication is essential to a firm's growth. It is something that enables executives conduct management's fundamental tasks planning, organizing, motivating, and controlling. Communication skills are the foundation of any company exercise, whether printed or verbal. Thus, efficient interaction is an organization's construction stone. Leadership interactions that are characterized by electronically-mediated communication between leaders and employees that are on different location are what is called ``remote’’ leadership. Throughout the practice of remote leadership, it is essential that a leader has the ability to develop a common vision where all the organization's employees also understand the shared vision but also accept and dedicate to it. Knowing the overall business situations is crucial to the operation of different businesses by general trading companies, and the profit and loss data is preserved for accounting purposes for each segment. countless businesses with differing features actually exist in one segment, Therefore, each company manages its business by splitting it further into smaller units. Nowadays a lot of new company implement remote leadership practice so the leaders can manage the company from a distance, one example of those aforementioned company is CV. Anugrah Driatama who runs in logistic services and general supplier industry. after the author conducted preliminary research, it is evident that the remoteleadership practice on CV. Anugrah Driatama is experiencing some communication problems. The author aimed to acknowledge the implementation of remote leadership in CV. Anugrah Driatama, to identify communication effectiveness through remote leadership in CV. Anugrah Driatama, and to investigate the most affecting factor of remote leadership towards communication effectiveness in CV. Anugrah Driatama. The author uses qualitative approach in this research by conducting interviews and focus group discussion. The analysis of the data is analysed through thematic analysis. The result of this research is that there are three variables that are born from the implementation of remote leadership and is affecting the communication effectiveness on the company. The three variables are leadership style, virtual leadership, and physical distance. It is evident that among the aforementionedthree variables, the one that have the most effect towards communication effectiveness within CV. Anugrah Driatama is virtual leadership. although the physical distance variable also get a lot of negative statements, almost all the problems always leads to the ineffective use of virtual leadership media that wasn’t able to replace the physical presence of the leader on the office.Key words: Communication Effectiveness, Leadership Style, Virtual Leadership, Physical Distance, Remote Leadership